2017
DOI: 10.1183/20734735.008817
|View full text |Cite
|
Sign up to set email alerts
|

The use of tracheal sounds for the diagnosis of sleep apnoea

Abstract: Tracheal sounds have been the subject of many research studies. In this review, we describe the state of the art, original work relevant to upper airways obstruction during sleep, and ongoing research concerning the methods used when analysing tracheal sounds. Tracheal sound sensors are a simple and noninvasive means of measurement and are more reliable than other breathing sensors. Developments in acoustic processing techniques and enhancements in tracheal sound signals over the past decade have led to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
(43 reference statements)
1
41
0
Order By: Relevance
“…FFT is applied on each segment with Hanning window (R seg (k)). Depending on the recording device, the main respiratory frequency band could be different [22]. In this study, as shown in Fig.…”
Section: B Frequency Domainmentioning
confidence: 95%
“…FFT is applied on each segment with Hanning window (R seg (k)). Depending on the recording device, the main respiratory frequency band could be different [22]. In this study, as shown in Fig.…”
Section: B Frequency Domainmentioning
confidence: 95%
“…TS signals correlate well with respiratory flow, with no significant difference in the number of apneas detected with TS or reference sensors [4,[6][7][8][9]. Tracheal sounds, recorded at the sternal notch, reflect the superficial vibrations of the body setinmotionbypressure fluctuations [10,11]. Placed on the sternal notch, the TS sensors can detect these vibrations and thus measure tracheal flow sound as well as snoring.…”
Section: Tracheal Sound Analysis For Detection Of Sleep Disordered Brmentioning
confidence: 97%
“…The authors' note that the algorithm's performance of 92% sensitivity and 98% specificity exceeds that of a piezo-electric film based acoustic method reported in the literature. Using tracheal sounds for apnea detection is an area of increased research and commercial interest, particularly with respect to the detection of sleep apnea [15].…”
Section: Ventilation and Respiratory Rate Monitoringmentioning
confidence: 99%